SEJARAH PERKEMBANGAN ORIENTALISME - Rahim, Abdul (State Institute of Islamic Studies (IAIN) Palu, 2010)
This article delas with the history of Orientalism. Orientalism in its history, passed three periods with their respective characteristics: (1) the heyday of Islam, Orientalism in this period was characterized by the transfer of knowledge and philosophy from the Islamic world to Europe (2) during the crusades until the time of enlightenment in Europe; orientalism in this time make Islam as the object of systematic study through translation, in this period the storiesÂ discrediting Â Islam also emerged, (3) the period of enlightenment in Europe until now, orientalism in this period began to shift into the realm of pure intellectual purpose to learn the middle east (Islam) as objective study.Kata Kunci: Orientalisme, Timur, Barat, Perang Salib